1994
DOI: 10.1128/iai.62.5.1726-1732.1994
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of the human formyl peptide receptor ligand-binding region

Abstract: The formyl peptide (N-formyl-1-methionyl-1-leucyl-1-phenylalanine [FMLP]) receptor is involved in the activation of neutrophils and their subsequent response to chemotactic N-formylated peptides. Recently, we found that the first extracellular loop closest to the N-terminal end of the FMLP receptor exhibited the strongest ligand binding compared with that shown by other extracellular regions. By constructing amino acid substitutional variants of this domain, we have determined that residues Arg-84 and Lys-85 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…A similar decrease (33‐fold) was observed when Lys85 was mutated to alanine; however, the extent of reduction was less than that observed with the Arg84 mutation. These two residues (Arg84 and Lys85) are located in the N‐terminal region of the first extracellular loop, thereby reconfirming previous synthetic peptide studies from our laboratory [17]. Mutating Asp284 to alanine resulted in a 23‐fold reduction in the binding affinity of the receptor.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A similar decrease (33‐fold) was observed when Lys85 was mutated to alanine; however, the extent of reduction was less than that observed with the Arg84 mutation. These two residues (Arg84 and Lys85) are located in the N‐terminal region of the first extracellular loop, thereby reconfirming previous synthetic peptide studies from our laboratory [17]. Mutating Asp284 to alanine resulted in a 23‐fold reduction in the binding affinity of the receptor.…”
Section: Resultssupporting
confidence: 81%
“…Mutating Asp284 to alanine resulted in a 23‐fold reduction in the binding affinity of the receptor. Asp284 is located in the C‐terminal region of the fifth extracellular loop of FPR, another region which has been implicated in ligand binding by peptide inhibition studies [17]. Mutating Arg205 and Arg163 also reduced the binding affinity by 58‐fold and 28‐fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is also suggested that part of the N-terminal domain, together with all of the first and part of the second extracellular loops, are spatially orientated so as to provide a ligand-recognition site (Figure 3). It is possible that the N-terminal subdomain forms a ' lid ' over the top of the ligand-occupied receptor as has been suggested for the formyl peptide receptor [27]. Such interaction with receptor extracellular domains has now been demonstrated for a variety of peptide ligands, from small formyl peptides to large glycoproteins [28][29][30][31][32][33][34][35].…”
Section: Figure 6 Dose-dependent Selective Inhibition Of Avp-stimulatmentioning
confidence: 99%
“…These charged moieties may function as important contacts in receptor-ligand interactions. 81 We have confirmed this by recombinant expression of a truncated FMLP receptor mutant.82 However, complete FMLP binding to the receptor appears to involve the other extracellular loops. 80 Multiple areas of ligand binding of the FMLP receptor have also been suggested by others.…”
Section: Chemotactic Receptors and Interaction With G Proteinsmentioning
confidence: 99%
“…[83][84] Likewise, activation of G proteins also requires the interaction of multiple intracellular portions of the receptor molecule with the G proteins themselves. [76][77][78][79][80][81][82][83][84][85] Interestingly enough, the second intracellular loop of the receptor molecule appears to play the major role in receptor-G protein interactions.76 Figure 1 depicts a diagram of the receptor.…”
Section: Chemotactic Receptors and Interaction With G Proteinsmentioning
confidence: 99%